Sustainable Compliance Programs In Complex Organizations (Global Journal of Management and Business Research, 2023)
I identify and test the empirical implications of complexity theory to investigate the effectiveness of the firm s risk management program in monitoring compliance program activity I provide a direct link between the quality of Business Regulatory Compliance Unit which executes and oversees the compliance program implementation and the overall risk management quality of the firm I use a multi-method design incorporating survey questionnaires and econometric multivariate analysis of a sample of European firms I find a relationship between the risk management exposure of European firms and the quality of their internal control department I also find a strong relationship between earnings at risk for UK firms and asset-liability at risk for financial firms but only a weak relationship between cash flow at risk and internal audit quality for European firms The quality of internal compliance business units is strongly positively related to corporate performance over time
Keywords: complexity theory; sustainable compliance; internal controls; information governance